1999
DOI: 10.2337/diacare.22.2.288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a thiazolidinedione compound on body fat and fat distribution of patients with type 2 diabetes.

Abstract: Treatment with the thiazolidinedione troglitazone in human patients with type 2 diabetes decreases intra-abdominal fat mass but does not affect total body fat or weight. This potentially valuable effect points to a differential action on insulin sensitivity in different adipose tissue depots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
169
1
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(188 citation statements)
references
References 0 publications
15
169
1
3
Order By: Relevance
“…Preadipocytes derived from subcutaneous adipose tissue express higher levels of PPARγ, C/EBPα and retinoid X receptor α (RXRα), and more readily proliferate and differentiate in vitro than cells from visceral fat depots (Table 1). In addition, these cells are more sensitive to TZD treatment in vitro, which is consistent with the selective increase in subcutaneous fat mass in patients treated with TZDs [32][33][34][35][36][37][38][39].…”
Section: Biological Differences Between Visceral and Subcutaneous Adisupporting
confidence: 78%
“…Preadipocytes derived from subcutaneous adipose tissue express higher levels of PPARγ, C/EBPα and retinoid X receptor α (RXRα), and more readily proliferate and differentiate in vitro than cells from visceral fat depots (Table 1). In addition, these cells are more sensitive to TZD treatment in vitro, which is consistent with the selective increase in subcutaneous fat mass in patients treated with TZDs [32][33][34][35][36][37][38][39].…”
Section: Biological Differences Between Visceral and Subcutaneous Adisupporting
confidence: 78%
“…21,28,47,52,53 This seemingly paradoxical effect for a class of drugs that improves IS is due to increased peripheral rather than visceral fat and thus should not confer the metabolic and inflammatory abnormalities associated with intraabdominal fat. 54 Pioglitazone treatment for 16 weeks caused a 4% increase in body mass index, an 11% increase in total fat mass, a 14% increase in subcutaneous fat mass, but a 9% decrease in intraabdominal fat and improved hepatic and peripheral IS. 55 By promoting maturation of adipocytes in peripheral fat depots, these drugs direct fat in inert storage sites rather than allowing excess trafficking of fatty acids from metabolically active visceral stores.…”
Section: Adverse Effects Of Glitazonesmentioning
confidence: 95%
“…11 -HSD1 -/-mice had higher adipose PPAR mRNA levels in their fat. Since PPAR ligands cause insulin sensitisation and fat M a n u s c r i p t 11 redistribution to the periphery (Kelly et al, 1999, Sewter et al, 2002, a mechanism for the beneficial fat redistribution was suggested, on the assumption that increased circulating free fatty acids during high fat feeding were acting as endogenous ligands for the PPAR receptors . In agreement with both increased PPAR and reduced glucocorticoid action, insulin sensitisation is evident in isolated primary 11 -HSD1 -/-adipocytes which showed increased basal and insulin-stimulated glucose uptake.…”
Section: -Hsd1 Deficient (-Hsd1mentioning
confidence: 99%